Plasma electrolytic fluorination on Mg alloys: coating growth and plasma discharge behaviour. (2nd November 2021) - Qi, Yuming; Peng, Zhenjun; Liang, Jun; Wang, Peng
ABSTRACT: In this work, plasma electrolytic fluorination (PEF) was performed on AZ91 alloy in a non-aqueous NH4 F-ethylene glycol (EG) electrolyte. The coating growth and the plasma discharge behaviour were investigated to understand the mechanism of PEF process. Results illustrated that the non-aqueous electrolyte determined the intrinsic characteristics of the PEF process, which resulted in the coating growth characteristics and plasma discharge behaviour distinct from those of a conventional PEO process. MgF2 compound formed from the combination of the oppositely charged ions Mg 2+ from the substrate and F- form the electrolyte. The deposition of MgF2 facilitated the growth of the PEF coating with an inward-growth characteristic. The discharge was characterised by a very small size and a weak intensity of the sparks, with an electron temperature (Te ) range of 3400∼3600 K. The three-type discharge model of conventional PEO processes was introduced to understand the mechanism of the PEF process.